China in Africa - Game Changer from the African Perspective? - David, Mfon-Obong Monday; Garlick, Jeremy; Havlová, Radka, 1975-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2019)
The thesis goal is to analysis the nature of China-Africa relation covering the historical aspect, dimensions of China's interest in the continent, its policy, cooperation mechanism as well as the impacts of their relation within the political and economic dimensions.
Vedoucí práce: Jeremy Alan Garlick
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses